Flexural behavior of reinforced concrete beams strengthened by HDC and RPC. (10th November 2018) - Deng, Mingke; Ma, Fudong; Ye, Wang; Li, Fangyuan
Highlights: Strengthening in the tension zone can improve the flexural capacity. Too many steel bars added may lead to similar over-reinforced beam failure. The beams strengthened in the compressive zone exhibit higher ductility. Strengthening effect is more obvious as the increase of reinforcement ratio. Abstract: Highly ductile fibre reinforced concrete (HDC) and reactive powder concrete (RPC) are characterized by tensile strain-hardening behavior and ultrahigh strength, respectively. This paper investigates the flexural behavior of reinforced concrete beams strengthened by HDC and RPC in the tension and compressive zones. The crack distribution, failure pattern, load-displacement responses, flexural capacity analysis, displacement ductility and concrete strain are investigated. The experimental results from monotonic loading tests on the specimens show that the flexural capacity of specimens strengthened by an HDC layer in the tension zone was notably increased and that the specimens strengthened by an HDC or RPC layer in the compressive zone exhibit much higher ductility than the control concrete beams. Moreover, the proposed calculation method of flexural capacity is more accurate, consistent and conservative.